Design of Gamification of Flood Early Warning Actions Using the "Cikeas – Cileungsi Overflow" Game in the KP2C Community - Sucipto, Adi; Kuswantoro, RBH; Christoffel, Christoffell (PROtek : Jurnal Ilmiah Teknik Elektro, 2023)
The role of the early warning system by the KP2C Community in providing information on flood disasters that often occur in the Cileungsi Ã¢â‚¬â€œ Cikeas watershed really helps the community in reducing the impact of the unavoidable flood disaster. The creation of the game Ã¢â‚¬Å“Cikeas Ã¢â‚¬â€œ Cileungsi OverflowÃ¢â‚¬Â aims to introduce knowledge about actions related to flood early warning to the wider community more effectively and fun. By using the gamification method, real activities carried out by KP2C such as interacting with residents through social media, monitoring the condition of upstream rivers, and providing disaster warnings, can be displayed in a simpler form into an educational game. The process of creating a game is carried out by conducting research on various types of KP2C activities in becoming an early warning instrument and then converting the data into a game mechanic. Through the results of game testing, 93.4% of respondents said the gameplay displayed in the game "Cikeas Ã¢â‚¬â€œ Cileungsi Overflow'' was quite interesting and 90% of respondents stated that their understanding of the concept of a flood early warning system had been conveyed well. There are still several aspects that need to be developed in the future from the "Cikeas Cileungsi Overflow '' game, especially the leaderboard mechanism which still has problems and continued development to the Android platform